English as Medium of Instruction at Physics International Class Program: A Study of Students’ Perception - Sitti Syakira (Indonesian TESOL Journal, 2020)
The specific focus of this paper is to uncover the students’ perception on English language use as the medium of instruction (EMI) in the teaching and learning at Physics International Class Program (ICP), State University of Makassar. The paper describes the students’ reason and expectation choosing ICP rather than regular one, their difficulties, as well as their language achievement. The data was collected using semi-structured interview to nine of third-year physical students in the program. The interviews were conducted in the language that the participant felt comfortable using (Indonesian) and recorded about seven to nine minutes each students. The analysis follows the qualitative content analysis described by Miles and Huberman, (1994): that is, themes were coded and categorized into the needs of the research, and patterns in the themes were identified and during this process, interpretations of these arrangements were made. The result of this study indicates that EMI in ICP helps some students to improve their English especially in writing, reading and vocabularies although some others are still experiencing difficulties in the teaching and learning process. Therefore, program development is still necessarily required in ICP in order to maintain its quality. Furthermore, the result of this study is expected to be a consideration for the continuity program in the future for a better service of its all aspects and to be a positive contribution for the next researcher who wants to conduct deeper research related to this topic.The specific focus of this paper is to uncover the students’ perception on English language use as the medium of instruction (EMI) in the teaching and learning at Physics International Class Program (ICP), State University of Makassar. The paper describes the students’ reason and expectation choosing ICP rather than regular one, their difficulties, as well as their language achievement. The data was collected using semi-structured interview to nine of third-year physical students in the program. The interviews were conducted in the language that the participant felt comfortable using (Indonesian) and recorded about seven to nine minutes each students. The analysis follows the qualitative content analysis described by Miles and Huberman, (1994): that is, themes were coded and categorized into the needs of the research, and patterns in the themes were identified and during this process, interpretations of these arrangements were made. The result of this study indicates that EMI in ICP helps some students to improve their English especially in writing, reading and vocabularies although some others are still experiencing difficulties in the teaching and learning process. Therefore, program development is still necessarily required in ICP in order to maintain its quality. Furthermore, the result of this study is expected to be a consideration for the continuity program in the future for a better service of its all aspects and to be a positive contribution for the next researcher who wants to conduct deeper research related to this topic.